Karakter Tax Avoidance dalam Memediasi Faktor-Faktor Ketepatan Waktu Penyampaian Laporan Keuangan - Erlita Nisrina; Choirul Anwar (Jurnal Ilmiah Wahana Akuntansi, 2020)
This study aims to obtain empirical evidence about the influence of company commissioners, profitability, leverage and company size along with tax avoidance as a moderating variable on the timeliness of financial statement submission in manufacturing companies in Indonesia. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2014-2018 with a total of 41 companies. The results of this study indicate that company commissioners, profitability and leverage have a significant effect on tax avoidance, while company size has no significant effect on tax avoidance as a mediating variable. Then the results of the tax avoidance intervention on the timeliness of financial reporting do not only show significant results but also do not mediate in character.